إستخدام التحليل الهرمي (AHP) في المفاضلة لإختيار المجهزين: دراسة حالة في الشركة العامة للمسح الجيولوجي والتعدين (Journal of Accounting and Financial Studies ( JAFS ), 2010)
Analytical Hierarchy Process (AHP) belongs to the family of Multiple Criteria Decision Making (MCDM)  and has, recently, received a wide popularity in decision making regarding supplier selection.  The objective of this study is to apply the methodology of AHP on selecting suppliers to supply materials for the  Geological Survey and Mining  Company (GSMC).  Criteria for rating the suppliers and pairwise comparisons were identified by the members of the Tenders Analysis Committee (TAC). In order to judge the internal validity of the AHP, it was applied manually on a sample of fourteen tenders that were analyzed  and executed between 2004-2007, then an interactive computerized  package was developed  using Access and Visual Basic to analyze the sample tenders.  The analysis conducted revealed that the suppliers who were selected by the TAC were the same suppliers chosen by the computerized AHP.  These results indicate the validity of the pairewise comparisons of the suppliers' selection criteria as well as the suppliers pairewise comparisons.  In addition the computerized package was able to select suppliers within seconds compared to the long time required by TAC to select suppliers.  The searchers recommend the application of the computerized AHP as a decision support tool in the process of supplier selection at the GSMC.